Professional business communication: the development of the concept (Pedagogy of Higher and Secondary Education, 2013)
Zotova-Sadylo H. Y. Professional business communication: the development of the concept.The article focuses attention on the issues associated with the development of «professional business communication» concept, its structure and specific features.
Keywords: professional business communication; specialist of economics; specific characteristics of the communicative process; business conversation; negotiations; business relations